SOSIALISASI PENGOLAHAN TELUR ASIN AYAM RAS DI DESA MARGO LESTARI, KECAMATAN JATI AGUNG KABUPATEN LAMPUNG SELATAN - Teguh Rafian; Miki Suhadi; Yuli Wahyu Tri Mulyani; Elia Agustiana; Kusuma Adhianto; Dian Kurniawati (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2023)
Margo Lestari Village is a village with potential as a laying hen farming center. This can be seen from the people who raise laying hens. However, the high egg production in the village is not matched by egg sales or marketing. This results in the production of eggs that can rot before being utilized or consumed because eggs have a fairly short shelf life. Thus, it is hoped that this service activity can increase the income of farmers through improving the quality of salted egg products from laying hen eggs in Margo Lestari Village. This counseling activity uses the lecture method and question and answer section. Extension activities were carried out on Wednesday, October 26, 2022 at 09.00 to 12.30 WIB at the Margo Lestari Village Hall, Jati Agung District, South Lampung Regency. The socialization was attended by 20 people, most of whom were breeders. After carrying out community service activities, it can be concluded that there are several things obtained by farmers as participants, namely increasing knowledge related to processing poultry farm products into salted eggs to increase the selling price and shelf life of production eggs in an effort to increase the economic value of farmers. Keywords: Processed Livestock Products, Economic Value, Egg Storability